Purwarupa Sistem Monitoring Tangki Bahan Bakar Genset pada STO dengan Metode Sensing Akumulasi Kecepatan Fluida (Studi Kasus PT. Telekomunikasi Indonesia) - Fahmi Farizal; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sentral Telepon Otomatis (STO) is a one of many communication structure belongs to PT. Telekomunikasi Indonesia with purpose to connecting or distributing data from one area to another area. When a STO is down it will be disturbing data distribution to/from another STO. So, PT. Telkom has a secondary power supply is a Genset. Unfortunately, PT. Telkom haven't tank measuring system, that giving a chance for fuel to stealed. On some of this considerations, the author conducted a research using technology to measuring fuel and send the result into database. The author applied a mini-pc with the type of Arduino UNO and feature it with ethernet shield that works for communication mediator data within database and a measuring system. The beginning of system is accumulating liquid per second that through 2 sensors. Result of this proccess, user can obtain result of measuring that can be calibrated so the result have higher accuracy. Accuracy of first sensor is between 92,3% and second sensor is between 95%. Then, result of measuring sent to the database with PHP called-self function and saved in the mySQL.